THE INFLUENCE OF SERVICE AND PRODUCT QUALITY ON CUSTOMER SATISFACTION AT GEPREK SAY BY SHANDY AULIA IN BENGKULU CITY - Nova Anggraini; Andriyani Prawitasari; Siti Hanila (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2021)
ABSTRACTThe purpose of this study is to determine the influence of service and product quality on consumer satisfaction at Geprek Say by Shandy Aulia in Bengkulu City. The analytical method used was Spearman rank correlation andÂ  hypothesis testing with a sample of 40 respondents. From the coefficient calculation of spearman rank correlation for the influence of service quality on customer satisfaction atGeprek Say By Shandy Aulia in Bengkulu City, the value of Ï is 0.608 which means strong, because the correlation value lies in the correlation coefficient interval 0.60 - 0.799. And from the hypothesis testing with the t test shows that t count >t table (4.718>1.685) then Ho is rejected and Ha is accepted, it means that service quality has a significant effect on consumer satisfaction at Geprek Say by Shandy Aulia in Bengkulu City. While the coefficient calculation of the spearman rank correlation for the effect of product quality on consumer satisfaction at Geprek SayÂ  By Shandy Aulia in Bengkulu City obtained a value of Ï of 0.591, which means that the effect of product quality on consumer satisfaction at Geprek Say By Shandy Aulia in Bengkulu City is moderate, because the correlation value lies in the interval correlation coefficient of 0.40 - 0.599. And from the hypothesis testing with the t test shows that t count >t table (4.011>1.685) then Ho is rejected and Ha is accepted, it means that product quality has a significant effect on consumer satisfaction at Geprek Say By Shandy Aulia in Bengkulu City.Keywords: Service Quality, Product Quality, Customer Satisfaction.